1989
DOI: 10.1038/clpt.1989.129
|View full text |Cite
|
Sign up to set email alerts
|

Effects of age on the serum concentration of α1-acid glycoprotein and the binding of lidocaine in pediatric patients

Abstract: We determined the effect of age on the serum concentration of alpha 1-acid glycoprotein (alpha 1-AGP) in venous blood from 134 subjects who ranged in age from preterm neonates to 18-year-old adolescents. The mean (+/- SD) serum concentration of alpha 1-AGP, determined by radial immunodiffusion, increased significantly with age: the concentration found in neonates was less than that found in infants which, in turn, was less than that found in older children (p less than 0.001). In addition, we determined the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0
3

Year Published

1990
1990
2014
2014

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 114 publications
(49 citation statements)
references
References 0 publications
5
41
0
3
Order By: Relevance
“…Cord AAG concentrations average 0.24 g/L compared to 0.60 g/L for normal adult plasma 14,16,23,24 , which results in an average ratio of 0.38 for AAG (Table 1). In contrast to HSA concentrations, AAG concentrations in the mother at delivery are similar to those of nonpregnant adults (Table 1).…”
Section: Protein Bindingmentioning
confidence: 99%
“…Cord AAG concentrations average 0.24 g/L compared to 0.60 g/L for normal adult plasma 14,16,23,24 , which results in an average ratio of 0.38 for AAG (Table 1). In contrast to HSA concentrations, AAG concentrations in the mother at delivery are similar to those of nonpregnant adults (Table 1).…”
Section: Protein Bindingmentioning
confidence: 99%
“…There is particular concern about toxicity in children aged less ........................................................................................................................................................................................................................................... than 6 months where drug elimination is very variable with diminished clearances and prolonged half-lives. In neonates and young infants, the volume of distribution of local anaesthetics is greater than in older children [101,102] which reduces peak plasma levels and decreases the potential for toxicity after single injections but increases the risk of drug accumulation after multiple boluses or an infusion, the blood-brain barrier is more permeable [103], there are reduced plasma protein concentrations especially alpha-1-acid glycoprotein, the predominant binding protein for bupivacaine, with consequent high levels of free drug [104,105]. Seizures have occurred because of excessive infusion rates over many hours with cumulation of bupivacaine.…”
Section: Rowney and E Doyle • Epidural And Subarachnoid Blockade mentioning
confidence: 99%
“…k g -1 bupivacaine is well below the toxic blood concentration of bupivacaine.13'14 However, with unrecognized intravascular injection, toxic blood levels may be achieved with doses of bupivacaine smaller than 2.5 mg. kg-l. 15 Although the threshold dose of bupivacaine that produces central nervous system side effects after rapid intravascular injection in humans has been reported as 1.6 mg.kg-l, 15 the dose that produces toxicity in children may be less since the free fraction of bupivacaine may be greater in neonates and infants than it is in adults. 16 A recent study demonstrated that the administration of 1.25 ml. kg -I of local anaesthetic in the caudal space resulted in excessive spread of analgesia in 30% of patients.…”
Section: Discussionmentioning
confidence: 99%